An Open and Scalable Method for Spatial Measurement of Blue Economies - Llewellyn, Lyndon E. (Frontiers in Marine Science, 2022)
Blue economies are measured by mining national statistics or economic modeling, requiring substantial capability and quality data, both of which are not universally available. The lack of harmonized methods hampers international comparisons and results are usually only attributable at the national scale. An alternative method is described here that leverages an open computing environment and data to quantify blue economies using marine night light producing measurements that are intercomparable and scalable from national to regional to global.